William Blake and the Myths of Britain - Whittaker, J. author. aut Link
XI, 215 p.
Keywords: William Blake and the Myths of Britain is the first full-length study of Blake's use of British mythology and history. From Atlantis to the Deists of the Napoleonic Wars, this book addresses why the eighteenth century saw a revival of interest in the legends of the British Isles and how Blake applied these in his extraordinary prophetic histories of the giant Albion, revitalising myths of the Druids and Joseph of Arimathea bringing Christ to Albion.